Flying Aerial Laboratory for water sampling in the Amazon Region of Ecuador (Innovation & Development in Engineering and Applied Science, 2024)
This paper presents a brief research related to the environmental problem of preventive monitoring of water sources in the Amazon region of Ecuador. As consequence, a proposal for an effective strategy is presented through the implementation of an Intelligent Aerial Laboratory LAI, consisting of an Unmanned Aerial Vehicle RPA and a water sample collection system. In order to guarantee an autonomous remote monitoring of aquatic environments, the LAI integrates a Human-Machine interface HMI that allows the operator on land station to interact through long-range communication protocols with the LAI, which fulfills its functionality through an integrated hardware and software architecture on board. This work presents the assembled LAI prototype, results of its exploitation in real conditions for physicochemical properties sensing, as well as a reflection towards future work on this topic.
Keywords: Unmanned Aerial Vehicle (UAV); Convertiplane; Water Monitoring; Collection system; Ecosystem conservation